Comparing the Outcomes of Ceftaroline plus Vancomycin or Daptomycin Combination Therapy versus Vancomycin or Daptomycin Monotherapy in Adults with Methicillin-Resistant Staphylococcus aureus Bacteremia-A Meta-Analysis - Chienhsiu Huang; Ihung Chen; Lichen Lin (MDPI AG, 2022)
Introduction: Combination therapy with daptomycin plus ceftaroline to treat methicillin-resistant Staphylococcus aureus bacteremia has been reported to reduce methicillin-resistant Staphylococcus aureus bacteremia-related mortality. The purpose of the current meta-analysis was to compare the clinical outcome of methicillin-resistant Staphylococcus aureus bacteremia in patients treated with daptomycin or vancomycin plus ceftaroline combination therapy versus daptomycin or vancomycin monotherapy. Methods: Studies were included if they directly compared the efficacy of daptomycin or vancomycin plus ceftaroline combination therapy with that of daptomycin or vancomycin monotherapy in the treatment of methicillin-resistant Staphylococcus aureus bacteremia in adult patients. Results: One randomized controlled trial and five retrospective studies were included in the meta-analysis. The combination therapy group had an in-hospital mortality, duration of bacteremia, and adverse event rate similar to those patients who had monotherapy. There was less bacteremia recurrence in the combination group. Initial combination therapy with ceftaroline for the treatment of methicillin-resistant Staphylococcus aureus bacteremia showed a trend of reducing the risk of in-hospital mortality in the current meta-analysis. Conclusions: Randomized controlled trials are needed to further study the role of initial combination therapy with daptomycin or vancomycin plus ceftaroline in the treatment of methicillin-resistant Staphylococcus aureus bacteremia.